Research on Crop Water Status Monitoring and Diagnosis by Terahertz Imaging - LI, BIN; Wang, Rong; Ma, Jianjun; Xu, Weihao (Frontiers in Physics, 2020)
Leaf water content (LWC) is regarded as an important indicator of crop health in agriculture. It is in great need to develop a rapid, non-destructive and accurate diagnosis method which can measure and assess water level of different types of crops. In this research, winter wheat leaves were selected and the reliability and applicability of THz imaging for destructive and non-destructive water status monitoring were studied. Based on the measured THz transmission amplitude, we find that the water loss in the distal region is less than that in the basal region during the nature dehydration process. A high correlation is shown between the transmitted THz signal and water content level measured by gravimetric weighing method during dehydration and after rehydration. The obtained results show that the water content in winter wheat leaves can be measured destructively and non-destructively with a high accuracy, using terahertz waves in transmission geometry, which suggests THz imaging can be a good potential tool to measure the water content to diagnosis crop health in agriculture in a rapid, non-destructive and accurate way.